An investigation into management’s reluctance in implementing audit recommendations and its effects to risk: a case study of National Railways of Zimbabwe. - Chinamasa, Tariro M. (Midlands State University, 2018)
The purpose of this study was to identify the causes of non-implementation of audit recommendations, with the aim of coming up with strategies and best practices for the effective implementation of audit recommendation. The study was inspired by the current position of NRZ’s inadequacy to fund projects, remunerate employees and accumulation of losses. Literature reviewed showed that the organization face high levels of risk which posed as a result of non-implementation of audit recommendations. NRZ management has not been giving due attention to audit recommendations and this has negatively affected the operations in the organisation and has been accumulating a net liability position to date. It is therefore imperative to identify challenges faced by management in implementing audit recommendations. The research study used a descriptive qualitative case study approach .The research population was drawn from the management and employees of a local based company. A judgemental sampling technique with a sample size of 25 respondents was used. Closed ended questionnaires and interviews were the instruments used to collect data. Tables, graphs and charts were used in presenting and analysing the data collected.The research findings showed that non-implementation of audit recommendations exposed the organisation to risks such as credit risk, fraud risk, and reputational risk. The research recommended that NRZ should adhere to the requirements of ISA 2402 – Audit recommendation and follow up since this standard helps to ensure audit recommendations are implemented before the organization can face high risk levels.